Identification of Good Practices in Long-Term Exercise-Based Rehabilitation Programs in Stroke Patients - Mameletzi, Dimitra; Anifanti, Maria; Baotić, Kristina; Bernetti, Andrea; Budinčević, Hrvoje; Žuna, Petra Črnac; Deligiannis, Asterios; Dennehy, Zekie; Ferrari, Andrea; Forgione, Dolores; Hrvoje, Jurlina; Ilardi, Maura; et al. (BioMed research international, 2021)
Physical activity is an important factor for primary and secondary stroke prevention. The process of stroke rehabilitation includes early and late physical activity and exercise, which prevents further stoke and improve patients' quality of life. MY WAY project, an ERASMUS+ SPORT program, is aimed at analyzing and developing or transferring best innovative practices related to physical activity and exercise enhancing health in poststroke patients. The aim of the study was to identify, analyze, and present the good practices and strategies to encourage participation in sport and physical activity and engage and motivate chronic stroke patients to perform physical activity changing their lifestyle and to maintain a high adherence to long-term exercise-based rehabilitation programs. Our results demonstrated that unified European stroke long-term exercise-based rehabilitation guidelines do not exist. It seems that low training frequency with high aerobic exercise intensity may be optimal for improved physical performance and quality of life in combination with a high adherence. It is important to optimize the training protocols suitable for each patient. The continuous education and training of the specialized professionals in this field and the presence of adequate structures and cooperation between different healthcare centers are important contributors. The clear objective for each country should be to systematically make the necessary steps to enhance overall exercise-based stroke rehabilitation attendance in the long term. Long-term interventions to support the importance of physical exercise and lifelong exercise-based rehabilitation in chronic stroke patients should be created, what coincides with the goal of the MY WAY project.
Keywords: Exercise Therapy; Exercise; Stroke Rehabilitation; rehabilitace po cévní mozkové příhodě; Randomized Controlled Trials as Topic; Humans; Stroke; randomizované kontrolované studie jako téma; terapie cvičením; cévní mozková příhoda; lidé; cvičení